A study of the types of learners' interaction and characteristics affecting students' satisfaction and academic performance in online instruction - Gutierrez, Ma. Teodora E.
The study seeks to identify and validate the elements that contribute to the successful delivery of online instruction in terms of types of learners' interaction and characteristics. The respondents of this study were forty-six students enrolled in Distance Education taking up a course in the Masters degree in Public Administration in a State University in the Philippines. Comprehensive Analysis from the survey questionnaire returned by the respondents resulted that under a qualitative course the appropriate combination of Learners' Interaction is Run 1, which refers to once a week interaction for one to two hours with the content, with the peers and with the instructor, this is adequate to achieve the learning objectives of the course. However, under a quantitative course the appropriate combination of learners' Interaction is Run 6, which refers to high level of interaction with the content and instructor; this provides the highest learning outcome as reflected in the mean final grade of 1.46. it only shows that in the quantitative course, instructor and course documents play a vital role in online instruction. Moreover, the overall rating of the learners in the course is between very satisfactory and good. Frequency of accessing the course website and frequency of learner to learner interaction had been found to be a strong predictor of students' satisfaction.